CFD Evaluation of Hot Stamping Die Cooling System - Zakaria, A; S. N Ibrahim, M; M.S. Dezfouli, M (International Journal of Engineering and Technology, 2018)
This paper presents the results of CFD analysis on a complex near optimized cooling channels of hot stamping die for automotive structural part. Near optimum design is acceptable since cooling channels design is limited by its machining constraints. The objective of this evaluation is thus to determine the efficiency the cooling system by monitoring its cooling rate during 8 seconds of the quenching process. The die and blank were modelled as 3D volume mesh in a closed position thus ignoring the blank history data prior to the stamping operation. Temperature distribution representing hardness of the simulated final part is compared with the actual stamped component. The same procedure was validated against another structural component of different cooling channel design. The results show temperature pattern after 8 seconds can be used to predict harness distribution of the final part, thus indicating the viability of this method to be used in cooling system design.Â Â Â